SENSOR SUHU BERBASIS BAHAN FERROELEKTRIK FILM Ba0,55 Sr0,45TiO3 (BST) BERBANTUKAN MIKROKONTROLER ATMEGA 8535 - Ridwan Siskandar (Jurnal Biofisika, 2013)
Growth of pure Ba0.55Sr0.45TiO3 (BST) film on p-type silicon (100) substrates with two treatments on the enhancement and depletion (pretreatment of the substrate which is heated up to first at a temperature of 800°C for 15 hours before the spilled  solution BST) with the method Chemical solution Deposition (CSD) and spin coating at 3000 rpm  rotational  speed  for  30  seconds.  Films  (both  on  the  type  of  enha ncement treatment and type of deples treatment) in put on top of the substrate is then heated at a temperature of 800oC, 850oC and 900oC for 15 hours . Of BST film obtained was then carried out the characterization of the value range, sensitivity, resolution BST films, the level of accuracy and hysteresis.  Results showed that 850 oC enhancement BST  film  is  the  best  film  that  can  be  used  as  a  temperature  sensor  to  read  the changes in the environment (temperature only)  ATMega8535 based microcontroller. Output (voltage generated) amplified by differential amplifier circuit and non-inverting amplifier.  Subsequently  processed  into  digital  data  output  on  the  Analog  Digital Converter  (ADC)  internalATMega8535.  Digital  data  is  processed  by  the microcontroller.  Visualization  using  measuring  16x2  Liquid  Crystal  Display  (LCD) display which can change the voltagein units of degrees  celsius ( oC)  when given a BST film temperature stimuli